Keefektifan Pembelajaran Mengidentifikasi Unsur-Unsur Teks Berita Menggunakan Metode EARTH dan PQRST Pada Peserta Didik Kelas VIII - Ratna N, Ai; Darmawan, Deni (Gunahumas, 2022)
The purpose of this study was to describe the effectiveness of learning to identify elements of news text with the EARTH method for class VIII students, to describe the effectiveness of learning to identify elements of news text using the PQRST method for class VIII students, and to find out which methods are more effective in identifying learning news text elements using the EARTH method and the PQRST method in class VIII students. The research design used in this study was a quasi-experimental design with nonequivalent control group design. The sample in this study were students of class VIII A and class VIII B of SMP Plus Mekarmukti. The research data used in the study were the test value before being given treatment (pretest) and the test value after being given treatment (postest) in the sample class. The results showed that the EARTH method was effective in learning to identify elements of news text because sig. (2tailed) was 0.000 so that sig 0.05, the PQRST method was effective in learning to identify elements of news text because sig. (2tailed) is 0,000 so that sig 0.05, the PQRST method is more effective in learning to identify elements of news text because the average value of the PQRST learning process is 85.18%, the average attitude value is 89.624%, and the average value The average on the results after being given treatment (posttest) is 80.15 while learning using the EARTH method has an average process value of 82.4025%, the average on attitude assessment is 88.144%, and the average acquisition on the results after being given treatment (postest) was 79.33.